Bone Formation in Psoriatic Arthritis: A Report from the GRAPPA 2013 Annual Meeting - Schett, Georg (Journal of Rheumatology, 2014)
The simultaneous presence of bone erosions and bony spurs (osteophytes, enthesophytes) in the joints of patients with psoriatic arthritis (PsA) suggests that the disease leads to enhanced bone resorption as well as increased bone formation, the latter of which has not been observed in patients with rheumatoid arthritis. At the 2013 Annual Meeting of the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA), members heard an update on the current research into the cytokine signature in PsA and its effects on new bone formation.
EVALuna2:12916